APLIKASI PEMBERIAN PUPUK ORGANIK CAIR DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays L).: PEMBERIAN PUPUK ORGANIK CAIR DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays L). - Geger Hapit Gumelar; Siswadi Siswadi; Kharis Triyono (Innofarm:Jurnal Inovasi Pertanian, 2022)
This iresearch iis iabout i“Application iof inasa ipoc ifertilizer iand ichicken imanure ion igrowth iand iyield iof isweet icorn i(Zea imays iL). ihas ibeen icarried iout ifrom iMay i22, i2021 ito iJuly i24, i2021 iat ithe iExperimental iGarden iof ithe iFaculty iof iAgriculture, iSlametRiyadi iUniversity, iSurakarta, iwhich iis ilocated iin iKadipiro iVillage, iBanjarsari iDistrict, iSurakarta iCity. iThis istudy iaims ito idetermine ithe ibest iuse iof iNasa iPOC iand ichicken imanure ion ithe igrowth iand iyield iof isweet icorn i(Zea imays iL). iThis istudy iused ia icompletely irandomized idesign i(CRD) iwhich iwas iarranged iin ia ifactorial imanner. iThe itreatment iconsisted iof i2 ifactors, ieach itreatment icombination iwas irepeated i3 itimes. iThe itwo ifactors iare: i(1) iNasa iPOC ifertilizer i(N) iwith i3 i(three) ilevels, inamely: iwithout iNasa iPoc ifertilizer i(N0), iNasa iPOC i15 iml/L i(N1), iNasa iPOC i30 iml/L i(N2) i, i(2) igiving ichicken imanure i(A) iwhich iconsists iof i4 ilevels, inamely: iwithout igiving ichicken imanure i(A0), igiving ichicken imanure i360 i​​grams/polybag i(A1), igiving ichicken imanure i720 igrams/polybag i(A2) i, igiving ichicken imanure i1080 igrams/polybag i(A3). iThe itwo itreatment ifactors iwere icombined ito iobtain i12 itreatment icombinations. iThe idata iwere ianalyzed iusing iAnalysis iof iVariety, ifollowed iby ithe iHonest iSignificant iDifference iTest i(BNJ) iat ithe i5% ilevel. iThe iresults ishowed ithat ithe iPOC inasa ifertilizer itreatment ihad ian ieffect ion ithe iweight iof ithe iwet istover iwith ithe ihighest iaverage ibeing i177.53 igrams, ithe iapplication iof ichicken imanure ihad ino ieffect ion iall iobservation iparameters. iThe idose iof iN2A3 itreatment i(POC iNasa i30 iml/L iand ichicken imanure i1080 igrams/polybag) igave ithe ihighest iaverage iof i12.67 istrands, ithe idose iof iN1A3 itreatment i(POC iNasa i15 iml/L iand ichicken imanure i1080 igrams/polybag) igave iThe ihighest iaverage inumber iof icobs iwas i3.00 ipieces iand ithe idose iof iN1A2 itreatment i(POC inasa i15 iml/L iand ichicken imanure i720 igrams/polybag) igave ian iaverage iweight iof icobs iwithout ihusks, iwhich iwas i558.67 igrams.